Dukungan Sosial Keluarga dengan Kepatuhan Minum Obat pada Penderita Kusta di Kabupaten Bondowoso - Agusstyawan, Farid Wahyudi (Jurnal Keperawatan Profesional, 2020)
Leprosy is a type of chronic and contagious disease that can cause disability. Factors related to leprosy treatment include patient knowledge, medication adherence, family support, access to health services and the role of health workers. The purpose of this study was to determine the relationship between family social support and adherence to taking medication for lepers in Bondowoso Regency by using a cross sectional design. using two analyzes namely univariate and bivariate with chi-square test (α = 0.05). The results showed that the characteristics of respondents were more in the productive age group and most were male. Most respondents have a history of completing primary / MI education and have a job. The most dominant type of leprosy is MB type and the level of disability is mostly at level 0 disability. Most respondents have good medication adherence levels and have family social support consisting of emotional support, assessment support, information support and instrumental support in the category well. Bivariate analysis using the chi-square test showed that there was a significant relationship between emotional support, assessment support, information support, instrumental support and adherence to taking medication for lepers (p-value = 0,000). This shows that emotional support, assessment support, information support and instrumental support influence the compliance of taking leprosy in Bondowoso Regency. Keywords: Family social support, Compliance with medication